Tracing Clostridium perfringens strains from beef processing of slaughter house by pulsed-field gel electrophoresis, and the distribution and toxinotype of isolates in Shaanxi province, China. (February 2022) - Jiang, Yanfen; Ma, Yinghui; Liu, Qianqian; Li, Tianmei; Li, Yiming; Guo, Kangkang; Zhang, Yanming
Abstract: The purpose of this study was to investigate the distribution and specify the transmission and cross-contamination of Clostridium perfringens ( C. perfringens ) in the beef slaughtering and butchering process. The prevalence of 21.2% (150/708) yielded 208 isolates of C. perfringens, including 80.8% type A and 19.2% type D, 0.4% (3/708) samples carried both type A and D strains, and 72.5% type D isolates carried both cpe and atyp . cpb2 genes . C. perfringens were identified through the whole slaughtering process but no type F ( cpe and cpa isolates) was found. 69 isolates were further analyzed and classified into 28 PFGE genotypes and clade I contained 94.2% isolates and 24 PFGE genotypes, which showed the genetic diversity and epidemic correlation. Our study traced C. perfringens contamination along the handling processes and showed a gradually ascending contamination rate during the whole process, revealing widespread cross-contamination from the feces and hides of slaughtered cattle to the carcass in the slaughtering workshop, so as from tools and personnel to meat of the cutting workshops. Strains from different slaughterhouses (regions) have high homology, and type A is the predominant toxinotype. It is necessary to monitor and control several key points of cross-contamination during slaughtering process to reduce a risk of C. perfringens infection. Highlights: C. perfringens exists in the whole beef slaughtering and butchering process with high prevalence (21.2%). Type A is the predominant toxinotype (80.8%) with PFGE genotype diversity, but type F is absent. Widespread cross-contamination of C. perfringens occurs from feces/hides to carcass and tools/personnel to meat. Transmission and contamination of C. perfringens was specified for the first time along the slaughtering process in China.